Development of Causative Treatment Strategies for Lacrimal Gland Insufficiency by Tissue Engineering and Cell Therapy. Part 2: Reconstruction of Lacrimal Gland Tissue: What Has Been Achieved So Far and What Are the Remaining Challenges?. (2nd October 2016) - Massie, Isobel; Dietrich, Jana; Roth, Mathias; Geerling, Gerd; Mertsch, Sonja; Schrader, Stefan
ABSTRACT: The lacrimal gland is located in the upper temporal compartment of the orbita, and along with the ocular surface, eye lids, and sensory and motor nerves forms the lacrimal functional unit (LFU). The LFU is responsible for producing, distributing, and maintaining the tear film in order to maintain a smooth, moist, and regular ocular surface epithelium such that appropriate refractive properties are achieved and the eyeball is protected against dust, debris, and pathogens. If the main lacrimal gland is impaired (due to either disease or injury), this balance is disrupted, and severe quantitative dry eye syndrome (DES) can develop. DES treatments remain palliative, with the most commonly used therapies being based on tear substitution, tear retention, and control of inflammation on the ocular surface. Causative treatments such as salivary gland transplantation have shown to reduce symptoms in very severe cases, however can cause problems on the ocular surface due to different properties of saliva and tears. Therefore, causative approaches for treating DES by regeneration or reconstruction of lacrimal gland tissue depending on disease severity seem highly appealing. This article reviews current approaches for in vitro reconstruction of lacrimal gland tissue. Finally, the limitations that must be overcome before a new, tissue-engineered therapy may be delivered to clinic will be discussed.